THE SALINITY OF THE SOILS ON THE WESTERN SLOPE OF THE BEJENEASA FARM – COTNARI - Mihai Alexandru; Denis Topa; Sorin Capsuna; Anca Elena Calistru; Feodor Filipov; Gerad Jităreanu (Agricultura)
Soil salinity is a measure of the minerals and salts that can be dissolved in water. The process of increasing the salt content is known as salinisation. The accumulation of salt in the rootzone of grapevines has negative effects on their growth and yield. At very high concentrations, soluble salt will even kill plants. Our studies were performed on the Bejeneasa Farm, Cotnari Vineyard, in the northeast part of Romania. The studied area is about 11.6 hectares. It is situated on the upper part of the slope. The absolute altitude ranges between 152 m and 172.5 m. The average annual precipitation and annual temperature values are 508.9 mm and 10.9℃, respectively. In order to highlight the causes of weak growth of the vine on the slope with a slope of 8% and with the western exposure, five soil profiles were made in representative locations following the cutting clearing of the vine plantation. The soil profiles were made after cutting the vine stems due to the growing stagnation and the small yields obtained from the grapes. The soil profiles were located in the upper and lower parts of the slope, both in the part with a uniform slope and on the diluvial–colluvial glacis located in the contact area with the land with a lower slope. From each soil horizon, soil samples were collected for laboratory analysis. The analytical data showed the presence of a high content of soluble salts. Laboratory data showed that there was weak salinisation in the soil starting at a depth of 30 cm. In the soil layers located at a depth of more than 50 cm, a soluble salt content of more than 1% (w / w-1) was noticed. We consider that the high content of soluble salts in the soil is one of the main causes that has severely limited the production of grapes in the vineyard.